The Scope of Midwifery Practice Regulations and the Availability of the Certified Nurse‐Midwifery and Certified Midwifery Workforce, 2012‐2016 - Ranchoff, Brittany L.; Declercq, Eugene R. (Journal of midwifery & women's health, 2020)
Introduction Studies have linked midwifery practice laws to the availability of midwives but have generally not related workforce data to potential demand for reproductive health services. We examined state regulatory structure for midwives and its relationship to midwifery distribution and vital statistics data at the state and county level. Methods Midwifery distribution data came from the Area Health Resources Files, distribution of women of reproductive age came from the US Census, and birth statistics came from US Natality Files from 2012 to 2016. Midwifery regulations were drawn from American College of Nurse‐Midwives Annual Reports. We used bivariate analysis to examine the relationship between state midwifery practice regulations and the number of midwives available in states and counties to potentially meet women's health care needs. Results Twenty states and the District of Columbia had autonomous practice regulatory frameworks, whereas 24 states had collaborative practice regulatory frameworks during the years between 2012 and 2016. Six states changed regulations during that period. In 2016, the number of midwife‐attended births per number of midwives in a state was not related to the regulatory framework. However, states with autonomous frameworks had 2.2 times as many midwives per women of reproductive age (P < .0001) and 2.3 times as many midwives per total births when compared with states with collaborative statutory frameworks (P < .0001). At the county level, 70.1% of US counties had no midwife. Of those states with autonomous practice, only 59.7% of counties had no midwives, compared with 74.1% in states with collaborative models (P < .0001). Discussion Midwives have the potential to help address the shortage of maternity and reproductive health service providers. Our research suggests that increasing the number of states with autonomous regulatory frameworks can be one way to expand access to care for women in the United States.